(untitled) - Banks, Erik (New York, N.Y., 2005)
Financial Lexicon is intended as a comprehensive financial reference book that explains the formal and informal terminology of finance. Structured as a dictionary, the book will contain clear and detailed explanations of common banking, finance and investment terms. It will include formal corporate business terms alongside the jargon that has entered business life. Terms defined in TFL will be drawn from all of the major sectors in the international capital markets and the financial industry.
Keywords: Finance,Finance,Managerial economics,Business law; Dictionaries,Acronyms,Dictionaries